Thermal Properties of Okra and bitter Gouard - Yadav, K C; Singh, K K; Madhyan, B L (Journal of Agricultural Engineering, 2005)
Specific and heat thermal conductivity of okra decreased linearly from 3.54 to 1.18 kg/kj degree C and 0.32 and 0.038 W/m degree C, respectively, with decrease in moisture content from 88 to 12%(w.b). The specific heat and thermal conductivity of bitter groud decreased linearly from 3.76 to 0.95 kg/kj degree C and 0.61 to 0.07 W/m degree C, respectively, with decrease in moisture content from 89 to 10% (w.b).